Effects of dietary tryptophan supplementation on rectal temperature, humoral immunity, and cecal microflora composition of heat-stressed broilers - Li, Qiufen; Ouyang, Jingxin; Deng, Chenxi; Zhou, Hua; You, Jinming; Li, Guanhong (Frontiers in Veterinary Science, 2023)
This trial aimed to determine the effects of tryptophan (Trp) on the rectal temperature, hormone, humoral immunity, and cecal microflora composition in broiler chickens under heat stress (HS). One hundred and eighty 18-day-old female Arbor Acres broilers were randomly divided into three treatment groups, with six replicates of ten birds in each replicate. The broilers were either raised under thermoneutral conditions (TN, 23 ±1°C) or subjected to heat stress (34 ±1°C for 8 h daily). The TN group received a basal diet, and another two heat-stressed groups were fed the basal diet (HS) or the basal diet supplemented with 0.18% Trp (HS + 0.18% Trp) for 21 consecutive days. The basal diet contained 0.18% Trp. Results revealed that HS increased the rectal temperature, serum epinephrine (EPI), and corticotropin-releasing hormone (CRH) concentrations (P < 0.05), reduced the bursal index, the levels of serum immunoglobulin A (IgA), IgG, IgM, and serotonin (5-HT) as well as the relative abundance of Actinobacteria in cecum (P < 0.05) compared with the TN group. Dietary supplementation of Trp decreased the rectal temperature, serum dopamine (DA), EPI, and the levels of CRH and L-kynurenine (P < 0.05), increased the bursal index, the levels of serum IgA, IgM, and 5-HT as well as the relative abundance of Ruminococcus torques group in cecum of heat-stressed broilers (P < 0.05) compared to HS group. In conclusion, dietary Trp supplementation decreased rectal temperature, improved cecal microbiota community and Trp metabolism, and enhanced humoral immunity of heat-stressed broilers.